Ethylene glycol as a new sustainable fuel for solid oxide fuel cells with conventional nickel-based anodes. (15th June 2015) - Qu, Jifa; Wang, Wei; Chen, Yubo; Wang, Feng; Ran, Ran; Shao, Zongping
Highlights: Ethylene glycol could be used as a sustainable fuel for solid oxide fuel cells. Ethylene glycol was beneficial in suppressing coke formation on Ni anode. A high power output of 1200 mW cm −2 was obtained with ethylene glycol at 750 °C. An excellent operational stability was obtained with ethylene glycol fuel. Abstract: In this study, renewable ethylene glycol (EG) was exploited as a potential fuel for solid oxide fuel cells (SOFCs) with conventional nickel yttria-stabilized zirconia (Ni–YSZ) cermet anodes for sustainable electric power generation. Carbon deposition behaviors over Ni–YSZ anodes under different carbon-containing atmospheres such as EG, glycerol, ethanol and methane were characterized through thermodynamic prediction, oxygen-temperature programmed oxidation and SEM–EDX analysis. EG was observed to be better than acetic acid and glycerol and much better than methane and ethanol in terms of carbon deposition. A calculation of the open-circuit voltages of EG-fueled SOFCs suggested that EG is a suitable fuel for SOFCs. A maximum power output of 1200 mW cm −2 at 750 °C was obtained from a cell operating on EG-steam fuel, which is only a little lower than that from a cell based on hydrogen fuel. The cell was further operated stably on an EG-steam gas mixture for 200 h with no apparent performance degradation, carbon deposition over the anode, Ni agglomeration, or change in the morphology of the anodes. The current study confirmed the practical applicability of EG as a direct fuel for SOFCs, which may have a great effect on future energy systems.